URGENSI PERLINDUNGAN HUKUM PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (PPPK) DALAM PEMUTUSAN HUBUNGAN KERJA OLEH PEMERINTAH - Andreas, Parda Doni; Haryono, Dodi; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Government employees with a work agreement (PPPK) are Indonesian citizens whohave met the requirements and are appointed based on the work needs of government agencies.Government employees with a work agreement are appointed by civil service developmentofficials (PPK) with a work contract. If the maximum contract term limit is not strictlystipulated, it is feared that there will be potential politicization of the extension of the PPPKcontract by irresponsible individuals and then termination of PPPK employment may alsooccur. because there is a downsizing of the organization or government policy which results ina reduction in PPPK, what compensation will PPPK receive when that happens and what arethe legal remedies for termination of employment.The purpose of writing this thesis is: first, to find out the legal protection for governmentemployees with work agreements (PPPK) who are affected by termination of employment(PHK) by the government. Second, to find out the legal remedies that can be taken bygovernment employees with work agreements (PPPK) who are affected by termination ofemployment (PHK) by the government. The research method in this thesis uses a normativejuridical type of research, namely research that focuses on examining the application of therules of law. rules or norms in positive law. The nature of this thesis research isresearchdescriptivewhich systematically describes the facts and characteristics of the objectbeing studied accurately. The data source used is the data sourcefirst, seconds andtertiary, Thedata collection method used in this research is firstly literature study, which is a technique forobtaining secondary data through documents related to the problem, objectives and benefits ofthe research, then after the data is collected it is then analyzed to draw conclusions.Based on the research results, PPPK preventive legal protection, old age security,severance pay and legal assistance, then if there is a downsizing of government organizations,PPPK whose competence is still needed and the relevant regional contract has not yet endedwill be transferred to a unit that needs it in accordance with its competence, repressive effortsas The form of protection is the State Civil Apparatus Advisory Body which has the authorityto receive, examine and make decisions on Administrative Appeals, the two PPK's legalremedies in the First Layoff, through an objection mechanism which is submitted in writing tothe superior official who has the authority to punish by including the reasons for the objectionand a copy of which is submitted. to officials who have the authority to punish. Second, throughan administrative appeal mechanism submitted to the State Civil Apparatus Advisory BodyKeywords: Officials, Government, Employment Agreement